Effects and Mechanisms of Taohong Siwu Decoction on the Prevention and Treatment of Myocardial Injury - Shao, Chang-Le; Cui, Guo-Hong; Guo, Hai-Dong (Frontiers in Pharmacology, 2022)
Taohong Siwu decoction (THSWD) is one of the classic prescriptions for promoting blood circulation and removing blood stasis. With the continuous in-depth excavation in basic and clinical research, it has been found that THSWD has made greater progress in the prevention and treatment of cardiovascular diseases. Mechanisms of the current studies have shown that it could prevent and treat the myocardial injury by inhibiting inflammatory reaction, antioxidant stress, inhibiting platelet aggregation, prolonging clotting time, anti-fibrosis, reducing blood lipids, anti-atherosclerosis, improving hemorheology and vascular pathological changes, regulating related signal pathways and other mechanisms to prevent and treat the myocardial injury, so as to protect cardiomyocytes and improve cardiac function. Many clinical studies have shown that THSWD is effective in the prevention and treatment of cardiovascular diseases related to myocardial injuries, such as coronary heart disease angina pectoris (CHD-AP) , and myocardial infarction. In clinical practice, it is often used by adding and subtracting prescriptions, the combination of compound prescriptions and combinations of chemicals and so on. However, there are some limitations and uncertainties in both basic and clinical research of prescriptions. According to the current research, although the molecular biological mechanism of various active ingredients needs to be further clarified, and the composition and dose of the drug have not been standardized and quantified, this study still has exploration for scientific research and clinical practice. Therefore, this review mainly discusses the basic mechanisms and clinical applications of THSWD in the prevention and treatment of the myocardial injury caused by CHD-AP and myocardial infarction. The authors hope to provide valuable ideas and references for researchers and clinicians.